Case report: A rare presentation of spinal teratoma in neonates: Two cases from Ethiopia - N. Tihitena; A. Mesay (Elsevier, 2017)
Teratomas are tumors with foreign tissues with a different biological behavior from the anatomic locations [1]. The sacrococcygeal region is one of the favorite sites for extra gonadal teratomas, which is also the commonest site for spinal teratomas [3]. Occurrence of teratomas at the lumbar area is a rare anatomical anomaly and its association with dysraphysm is rarely described [5]. Here we report 2 cases; the first skin covered and the second multicystic lumbar mass with dural extension and spinal dysraphysm. Both have other associated anomalies. Both patients had satisfactory surgical outcomes.